Herding Dynamics, Volatility, and Market Capitalization: Implications for Stock Returns in Indonesia - Pranata, Rengga Madya; Waspada, Ikaputera; Nugraha, Nugraha; Purnomo, Budi S (JASF: Journal of Accounting and Strategic Finance, 2024)
This research examines the connections between herd mentality, price fluctuations, and company size in relation to stock performance for firms listed on the IDX from January 2019 through December 2023. The LSV approach is employed to quantify herding behavior, while historical data is used to calculate volatility. The study investigates how market capitalization and volatility influence the link between herd mentality and stock returns. Weekly stock prices, company valuations, trading volumes, and sales proportions from TradingView comprise the dataset. Findings indicate that market capitalization significantly enhances the relationship between herd behavior and stock returns, particularly for large-cap enterprises. Conversely, volatility weakens this relationship, with herd behavior's impact on stock returns diminishing in turbulent market conditions. These results highlight the significance of company size and market volatility in comprehending group investor conduct and its effects on stock market outcomes. The study's implications include the creation of more flexible investment tactics and market regulations that promote stability across various market scenarios.